Effect of Supportive Care Activities on Negative Emotional Feelings of Children with Nephrotic Syndrome (Medico Legal Update, 2021)
Nephrotic syndrome is a collection of symptoms due to kidney damage. This includes protein in the urine,low blood albumin levels, high blood lipids, and significant swelling. Other symptoms may include weightgain, feeling tired, and foamy urine. Complications may include blood clots, infections, and high bloodpressure.Aim of the study: This study was aimed to assess the effect of supportive care activities on negative feelingsof nephrotic syndrome children. Setting: The study was carried out at medicine department of children’shospital affiliated to Ain Shams University Hospitals. The subjects: The subject of this study was purposivesample composed of (50) children were attended to the previously mentioned setting and accompanyingmothers. Tools of data collection: An Interviewing Questionnaire, Children’s Assessment of Participationand Enjoyment (CAPE),multidimensional Scale of Perceived Social Support (MSPSS).Results: Less than half of the studied children having negative Emotional Feelings.Conclusion: The study concluded that the studied children with Nephrotic Syndrome have negative feelingsneed Supportive Care.Recommendations: This study recommended the importance of Encourage use of Supportive care activitiesprograms to help them to prevent the negative feelings of Nephrotic syndrome children.